2012
DOI: 10.5487/tr.2012.28.3.139
|View full text |Cite
|
Sign up to set email alerts
|

A Transfer of Silver Nanoparticles from Pregnant Rat to Offspring

Abstract: Silver nanoparticles (size: 7.9 ± 0.95 nm, dosage: 250 mg/kg) were orally administered to pregnant rats. At 4 days after parturition, four pups were randomly selected (one pup from one dam) and silver level in liver, kidney, lung and brain was determined by ICP-MS and electron microscope. As results, silver nanoparticles highly accumulated in the tissues of the pups. Silver level in the treated group was 132.4 ± 43.9 ng/g in the kidney (12.3 fold compared to control group), 37.3 ± 11.3 ng/g in the liver (7.9 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…The silver was possibly transferred from the pregnant rats. In a study performed by Lee et al (2012), Ag-NPs (size: 7.970.95 nm) were orally administered to pregnant rats (dosage: 250 mg/kg) and silver was found accumulated in the brain of the offspring (31.17 4.3 ng/g, 5.4 fold as compared to the control). It remained unclear whether Ag-NPs could penetrate the blood-brain barrier (BBB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silver was possibly transferred from the pregnant rats. In a study performed by Lee et al (2012), Ag-NPs (size: 7.970.95 nm) were orally administered to pregnant rats (dosage: 250 mg/kg) and silver was found accumulated in the brain of the offspring (31.17 4.3 ng/g, 5.4 fold as compared to the control). It remained unclear whether Ag-NPs could penetrate the blood-brain barrier (BBB).…”
Section: Discussionmentioning
confidence: 99%
“…It's reported that Ag-NPs could be transferred from pregnant rat to offspring (Lee et al, 2012). Earlier study showed that silver could cross the placenta and concentrate in the human fetus, achieving higher concentrations than in the mother (Lyon et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Silver has been shown to cross the blood brain barrier as well as the cerebrospinal fluid barrier to enter tissues of the central nervous system in animals (Lansdown 2007). Following oral AgNP administration in pregnant rats, silver was found to reach the offspring's brain (Lale Ataei and Ebrahimzadeh-bideskan 2014, Lee, et al 2012, Wu, et al 2015). After prenatal exposure to AgNP, silver was detected in hippocampus tissues of offspring, as was cell apoptosis (Lale Ataei and Ebrahimzadeh-bideskan 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the authors concluded that repeated ingestion of nano-sized AgNPs may induce organ toxicity and inflammatory responses in mice. Lee et al (2012) observed the transfer of silver from female rats to offspring after oral administration of 250 mg/kg BW /day of 8 nm silver nanoparticles, suggesting that silver crosses the placenta. Yu et al (2014) investigated the potential effects of AgNPs on pregnant rats and embryo-fetal development after maternal exposure on gestational days (GD) 6-19.…”
Section: Toxicity and Toxicocinetics Of Agnps After Oral Intakementioning
confidence: 92%